Peran Intermediasi Pasar Modal Dalam Meningkatkan Partisipasi Investor Di Pasar Modal Indonesia - Harrington B. Silaban; Eka Valentina Manurung; Regita Amelia; Yemima Eleonore Nadapdap; Putri Kemala Dewi Lubis (Universitas Kristen Indonesia Toraja, 2024)
The role of capital market intermediation on economic development cannot be denied, especially in relation to investor participation in the Indonesian capital market. This study aims to examine the effect of intermediation on investor engagement. To collect data, a qualitative descriptive method was used, mainly through an extensive literature review. The results of this study emphasize the importance of the role of various capital market intermediary institutions, including underwriters, securities trading intermediaries, securities companies, investment managers, custodian banks, and investment advisors, in encouraging greater investor participation in the Indonesian capital market. Simplifying the investment process and reducing costs are key strategies to attract more investors, especially individuals and beginners. Improving financial literacy among the general public is also important to understand the benefits and risks associated with investing, ultimately leading to wider and sustained investor participation. Recommendations include simplifying investment procedures, lowering fees, and promoting financial education initiatives.